Pengembangan Modul Literasi Digital Perlindungan Data Pribadi Berbasis Proyek untuk Menguatkan Kemampuan Berpikir Kritis Siswa - Anggita Dwi Puspitasari; Andreas Erwin Prasetya (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The research was conducted based on the results of a needs analysis that showed the unavailability of a personal data protection digital literacy module to strengthen critical thinking skills for elementary school students. The purpose of the research was to develop a personal data protection digital literacy module to strengthen critical thinking skills for elementary school students using a project-based learning (PjBL) model. The type of research used is research and development with the ADDIE model. The research involved 5 validators and 8 grade 5 elementary students. Data analysis used qualitative and quantitative data analysis. Data collection methods were participatory and non-participatory observation, closed questionnaires, structured interviews, and tests. The results showed 1) the development of a personal data protection digital literacy module for elementary students using the ADDIE stages (Analyze, Design, Development, Implementation, Evaluation), 2) the personal data protection digital literacy module has 'very good' quality 3) the personal data protection digital literacy module for elementary students helps students understand digital literacy and strengthen 21st century critical thinking skills.